Virgil in the Renaissance - Wilson-Okamura, David Scott, 1970- (Cambridge, UK ; New York : Cambridge University Press, 2010)
"The disciplines of classical scholarship were established in their modern form between 1300 and 1600, and Virgil was a test case for many of them. This book is concerned with what became of Virgil in this period, how he was understood, and how his poems were recycled. What did readers assume about Virgil in the long decades between Dante and Sidney, Petrarch and Spenser, Boccaccio and Ariosto? Which commentators had the most influence? What story, if any, was Virgil's Eclogues supposed to tell? What was the status of his Georgics? Which parts of his epic attracted the most imitators? Building on specialized scholarship of the last hundred years, this book provides a panoramic synthesis of what scholars and poets from across Europe believed they could know about Virgil's life and poetry"--Provided by publisher.
"Do not let me hear Of the wisdom of old men, but rather of their folly. It is a rich tale and strange, even for one poet, and when that poet is Virgil, a central author in the European tradition, the interest - and the intricacy - are both magnified"--Provided by publisher.
Machine generated contents note: Introduction; Part I. Publication: 1. Virgil with an i; Part II. Reputation: 2. Patronage and the Eclogues; 3. Variety and the Georgics; 4. Morals and minimalism; Part III. Interpretation: 5. Virgil's Odyssey; 6. Virgil's Iliad; Epilogue; Appendix A. Virgil commentaries (alphabetical); Appendix B. Virgil commentaries (ranked).
Includes bibliographical references and index.
Keywords: Virgil -- Appreciation -- Europe; Virgil -- Influence; European literature -- Renaissance, 1450-1600 -- Classical influences; Literature, Medieval -- Classical influences; Authors and readers -- Europe -- History -- To 1500.; Authors and readers -- Europe -- History -- 16th century